The metabotropic glutamate receptor 5 negative allosteric modulator fenobam: pharmacokinetics, side effects, and analgesic effects in healthy human subjects - Cavallone, Laura F.; Montana, Michael C.; Frey, Karen; Kallogjeri, Dorina; Wages, James M.; Rodebaugh, Thomas L.; Doshi, Tina; Kharasch, Evan D.; Gereau, Robert W. (Pain (Amsterdam), 2020)
Metabotropic glutamate receptor 5 (mGlu5) has been shown to modulate nociception in animals, but no mGlu5 antagonists have been developed commercially as analgesics. The mGlu5 antagonist fenobam [N-(3-chlorophenyl)-N′-(4,5-dihydro-1-methyl-4-oxo-1H-imidazole-2-yl)urea] was originally evaluated for development as a nonbenzodiazepine anxiolytic. Fenobam is analgesic in numerous mouse pain models, acting exclusively through mGlu5 blockade. Furthermore, fenobam showed no signs of analgesic tolerance with up to 2 weeks of daily dosing in mice. Analgesic effects of fenobam in humans have not been reported. The purpose of this investigation was to evaluate fenobam pharmacokinetics and analgesic effects in humans. We first evaluated single-dose oral fenobam disposition in a parallel-group dose-escalation study in healthy volunteers. A second investigation tested the analgesic effects of fenobam in an established experimental human pain model of cutaneous sensitization using capsaicin cream and heat, in a double-blind placebo-controlled study. The primary outcome measure was the area of hyperalgesia and allodynia around the area applied with heat/capsaicin. Secondary outcome measures included nociception, measured as pain rating on a visual analog scale, heat pain detection threshold, and effects on cognition and mood. Fenobam plasma exposures showed considerable interindividual variability and were not linear with dose. Fenobam reduced sensitization vs placebo at a single timepoint (peak plasma concentration); we found no other difference between fenobam and placebo. Our results suggest highly variable fenobam disposition and minimal analgesic effects at the dose tested. We suggest that future studies testing analgesic effects of mGlu5 blockade are warranted, but such studies should use molecules with improved pharmacokinetic profiles.